Characterization of β-tricalcium phosphate derived from green mussel shells (Molarity variation) - Santoso, Hillary Aurenne; Eddy, Eddy; Kesnatri, Manuel Romario; Putri, Tansza Setiana; Dipankara, Jackson; Nugroho, Astri Rinanti; Thi, Bang Le (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
β-Tricalcium phosphate (β-TCP) is a widely used bioceramic material. In dentistry, it is commonly used as bone graft material. β-TCP is osteoconductive, bioresorbable, bioactive, and has biocompatibility properties. This study aims to evaluate the optimum molarity of CaO and H3PO4 to synthesize β-TCP from a natural source (Perna viridis linn). This is laboratory experimental research conducted by reacting calcium compounds from green mussel shells and phosphoric acid using the dissolution precipitation method with variations in molarity ratio. X-ray diffraction (XRD), scanning electron microscope (SEM), and fourier transform infrared (FTIR) were used to identify the characteristics of β-TCP synthesized from green mussel shells. The XRD chart pattern showed the formation of peaks identical to the β-TCP (Sigma-Aldrich). However, formation of whitlockite phase was also seen in the results. FTIR results showed that phosphate, hydroxyl, and carbonyl groups were shown on the graph and could be identified as β-TCP. SEM characterization showed that the sample consisted of small particles irregularly shaped to form like aggregates. β-TCP synthesized using molarity ratio of 0.6M CaO: 0.4M H3PO4 had characteristics resembling β-TCP (Sigma-Aldrich).